Pengaruh Daya Listrik Oven Gelombang Mikro terhadap Pemecahan Emulsi Minyak Mentah Cepu - Ir.Wasir Nuri,MT (Eksergi)
Steam which injected to the oil well form a water in oil emulsion (W/O), emulsion must be broke to oil and water phase because disturb oil processing in the refinery unit. The emulsion stability depends on pH, water salinity, temperature and asphaltene, resin and wax content. This research are to find breaking effectiveness emulsion crude oil from Cepu and compare with usual oven. In this research water crude oil emulsion made from Cepu oil well with water salinity 20 ppt. Further the emulsion is affected using microwave radiation from microwave apparatus with variation electric power from 54to 432 Watts. Emulsion breaking with microwave more effective considered with effects use conventional oven. Research showed that increasing electrical power caused produce percentage emulsion breaking increase and faster. Demulsification emulsion formed water salinity 20 ppt in microwave oven with electrical power 432 Watt is the fastest breaking with broke reach 100 percents in five minutes. While demulsification with electrical power 54 Watt the longest breaking, during nineteen minutes break 100 percents. While using conventional oven needs 40 minutes for breaking 100 percents. This results show that emulsion breaking use microwave process more effective considering with use of conventional oven.